Berberine and health outcomes: an overview of systematic reviews - Lanjun Shi; Wenya Wang; Chengyang Jing; Jing Hu; Xing Liao (BMC Complementary Medicine and Therapies)
Abstract Background Berberine is an isoquinoline alkaloid isolated from Chinese herb coptis chinensis and other berberis plants which can be used to treat a wide range of chronic diseases. However, the current research evidence on the therapeutic effects of berberine has not been summarized. We aimed to synthesize the current evidence on the systematic review (SRs) of berberine for the treatment of diverse conditions. Methods A comprehensive search of the Cochrane Library, PubMed, EMBASE, Web of Science, CNKI, Wanfang, VIP, and SinoMed was performed from the database inception to April 11, 2024. SRs on berberine were included and evaluated. The methodological quality and the reporting quality of each SR were assessed using the AMSTAR-2 tool and PRISMA checklist, respectively. The quality of evidence was appraised based on the GRADE. Results Fifty-four SRs were included and analyzed. Overall, associations were found between berberine and 70 health outcomes concerned with 9 diseases. Berberine has improved most outcomes of these diseases: 78% (25/32) cardiovascular disease outcomes, 92.59% (25/27) type 2 diabetes mellitus outcomes, 94.74% (18/19) gastrointestinal disorders outcomes, 72.22% (13/18) polycystic ovary syndrome (PCOS) outcomes, 86.67% (13/15) non-alcoholic fatty liver disease (NAFLD) outcomes, 92.31% (12/13) schizophrenia outcomes, 90.91% (10/11) metabolic syndrome outcomes, 57.14% (4/7) obesity outcomes, and 100.00% (6/6) dyslipidemia outcomes. There was a high overlap of primary studies (CCA > 15%) in the SRs of PCOS, NAFLD, obesity, and schizophrenia. Only one SR was rated as high quality while eight SRs were rated as low quality and forty-five SRs as very low quality according to AMSTAR-2. Regarding the reporting quality, Item 14, 15, 21, and 22 were poorly reported for the included SRs in terms of PRSMA assessment. For GRADE, eight outcomes were rated as high quality evidence, twenty-two outcomes were rated as moderate quality, and 110 outcomes were rated as low quality. Conclusion Current evidence suggests that berberine has beneficial effects on a range of health outcomes for people with chronic diseases. Specifically, berberine significantly improves type 2 diabetes, gastrointestinal disorders, schizophrenia, metabolic syndrome, and dyslipidemia outcomes. However, caution is needed considering the shortcomings in the quality of the relevant system reviews included.